TELETANDEM: STUDENT’S BELIEFS AND ANSWERS - Telles, João Antônio (2011)
This article is one of a series of others that are currently being carried out within the context of the project Teletandem Brasil: Foreign languages for all. Developed at São Paulo State University, Brazil. The project focuses on the communicative processes of distance in-tandem language learning. The article focuses on a few successful and unsuccessful cases of teletandem. Data analyses are grounded on the hermenutic phenomenological mode of qualitative research. Our aim is to understand which aspects contribute and obstruct the online distance interaction of teletandem. The case studies focus on the problems that the students face and our attempt to provide explanations and to propose solutions. Some of these problems were linked to the students’ beliefs of autonomy and motivation. We conclude the article by providing a reflection on virtual in-tandem teaching/learning.